2013
DOI: 10.4097/kjae.2013.65.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of midazolam dose and age on the paradoxical midazolam reaction in Korean pediatric patients

Abstract: BackgroundAlthough midazolam administration may occasionally induce a paradoxical episode, such as threatened crying and violent behavior in children, systematic studies on the causes of paradoxical reaction are limited. We investigated the effect of children's age and a dose of midazolam on the paradoxical reaction.MethodsA total of one hundred sixty four children of 1-3 years and 3-5 years, were enrolled in this study. Each age group randomly received 0.05 mg/kg or 0.1 mg/kg of intravenous midazolam (41 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
1
23
0
2
Order By: Relevance
“…This reaction with midazolam has been associated with age, with the highest incidence found in children 1-3 years of age (29.3%), decreasing as the child ages. 8 Given these limitations, evaluation of alternative strategies for minimizing the development of anxiety in children is warranted. Additional studies evaluating other medications are limited, however, utility has been demonstrated for dexmedetomidine, 9 clonidine, 10 and intranasal sufentanil.…”
Section: Some Children Verbalize Their Fears While Others Show Behavimentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction with midazolam has been associated with age, with the highest incidence found in children 1-3 years of age (29.3%), decreasing as the child ages. 8 Given these limitations, evaluation of alternative strategies for minimizing the development of anxiety in children is warranted. Additional studies evaluating other medications are limited, however, utility has been demonstrated for dexmedetomidine, 9 clonidine, 10 and intranasal sufentanil.…”
Section: Some Children Verbalize Their Fears While Others Show Behavimentioning
confidence: 99%
“…Furthermore, some children may develop agitation after receiving oral midazolam secondary to the associated behavioral disinhibition. This reaction with midazolam has been associated with age, with the highest incidence found in children 1‐3 years of age (29.3%), decreasing as the child ages . Given these limitations, evaluation of alternative strategies for minimizing the development of anxiety in children is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…No defi nitive evidence is available for the number of children sedated with midazolam that exhibit this state, and likewise, little documentation for the duration of this response is readily available. It is the author's opinion that this angry child response occurs in approximately 20 % and lasts for 1-2 h. There is some evidence that this response tends to be inversely related to the age of the child (e.g., more frequent in 2-year-olds) [ 6 ]. Also, some evidence exists to suggest that fl umazenil will reverse the paradoxical reaction [ 7 ].…”
Section: Clinicalmentioning
confidence: 99%
“…Though rare, the case report literature includes observations of atypical response to nearly every agent in the benzodiazepine family, with intravenous midazolam being the most represented [ 1 4 ]. Interestingly, despite an association between risk factors and advanced age, the authors observed more reports of atypical responses in pediatric populations than in geriatric populations [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%